Non-formal integration of migrants and refugees in Portugal - Projeto Integrararte - Faria, Maria João (2020)
The Portuguese State guarantees refugees access to the school subsystem and to the National Health Service (SNS), with almost silent projects in the medium-long term in the non-formal and informal sphere. The research was carried out with two refugee families and the methodology adopted was action-research method. On a weekly basis, several activities into workshops were carried out that focused, not exclusively, on art, taking into account the United Nations Sustainable Development Goals for 2030, and those of the 2018 European Year of Cultural Heritage. It turned out to be a powerful tool that stimulated the ability to express the most diverse emotions, feelings and thoughts in a beautiful and simple way.